Institutional objectives and patterns of student change - Chickering, Arthur W.; Goddard Coll., Plainfield, VT. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
College objectives were redefined and student change examined to determine whether--(1) students change in college, (2) when and where change occurs, and (3) developmental principles which could apply to student change to facilitate decisions. Definitional activities yielded six major subcategories of behaviors and student characteristics--goal directedness, personal stability and integration, venturing, resourcefulness and organization, full involvement, motivation and persistence, and interdependence. To describe the timing and patterns of student development, faculty studies of student records were undertaken with a prepared question framework. Most change was found to occur during the first two years of college. The patterns of various vectors of change are described. Development occurs according to generalizable sequences, and through sequences of differentiation and integration. Development is congruent rather than compensatory. Development also decreases as relevant conditions become more constant. The relevance of these findings for institutions planning innovation and experimentation is discussed. Questions arising from the findings are also reviewed. (ps)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classification; College Role; College Students; Discriminant Analysis; Rating Scales; Research Projects; Statistical Analysis; Student College Relationship; Student Development; Student Records